The Influence of Pressure, Opportunity, Rationalization, and Ability on Academic Fraudulent Behavior of FEB Student - Ofhi Sabriana; Robith Hudaya (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the influence of factors in fraud diamond theory, namely pressure, opportunity rationalization, and ability, on student academic fraud behavior from the perspective of fraud diamond theory. The study used nine departments at the Faculty of Economics and Business with the acquisition of 373 data obtained, which were processed using Smart PLS. The results showed that pressure has a positive but insignificant effect on student academic fraud behavior, and rationalization significantly impacts student academic fraud behavior. In contrast, opportunities and abilities do not significantly impact academic fraud behavior